The Effectiveness of Group Counseling with a Self-Instruction Technique to Increase Self-efficacy of Vocational School Students - Tati Indaryanti; Edy Purwanto; Awalya Awalya (Jurnal Bimbingan Konseling, 2024)
Low self-efficacy can negatively affect academic achievement in vocational school students. In this way, this current research attempted to examine the implementation of group counseling with a self-instruction technique to students’ self-efficacy by changing irrational thinking into the rational one. It used a pretest-posttest control group design. Here, students’ data were collected using the General Self-Efficacy Scale (GSES). Previously, the sixteen students were divided into, namely  students in the experimental group and eight others in the control group. The students’ data were analyzed using the mixed anova. Based on the findings, the implementation of the group counseling with a self-instruction technique has been effective for increasing self-efficacy in vocational school students. Thus, counselors are recommended to apply a self-instruction technique to increase self-efficacy.